2014
DOI: 10.5812/jjm.11134
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydophila pneumoniae Infection Assessment in Children with Adenoid Hypertrophy Concomitant with Rhino Sinusitis

Abstract: Background:Since adenoids may act as a reservoir for bacteria, they can cause ear infection, recurrent otitis and recurrent adenotonsillitis. Therefore, adenotonsillectomy is an efficient method for reducing the number and severity of subsequent infections.Objectives:This study aimed to determine the Chlamydophila pneumonia infection by serological tests and performing PCR in the adenoid tissue, in children undergoing adenoid surgery and compare the results with normal children.Patients and Methods:This case c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
0
4
0
6
Order By: Relevance
“…Javadi Nia et al. [ 33 ] determined the prevalence of C. pneumoniae in children with adenoid hypertrophy concomitant with rhinosinusitis. In their study the pathogen was detected in 13.5% of patients using PCR, but their target group is completely different from ours.…”
Section: Discussionmentioning
confidence: 99%
“…Javadi Nia et al. [ 33 ] determined the prevalence of C. pneumoniae in children with adenoid hypertrophy concomitant with rhinosinusitis. In their study the pathogen was detected in 13.5% of patients using PCR, but their target group is completely different from ours.…”
Section: Discussionmentioning
confidence: 99%
“…The indication to perform at first a simple adenoidectomy (tonsillectomy is not indicated) is due to the strong relationship that exists between AH and CRS. Some authors prefer to speak of relationship between CRS and adenoiditis [18,19,20] rather than between AH and CRS, but most prefer the latter, in consideration of the etiology of AH as a likely consequence of chronic adenoiditis [17,21,22,23]. Over the past few years, several authors demonstrated the correlation between AH and CRS through different types of studies, based on the endoscopic study of the adenoid volume [24] on the same bacterial strains both on the adenoidal tissue and in the nasal sinuses [20,22,23,25,26,27,28] on the positive effects on CRS by adenoidectomy [21,29,30,31] on specific immunologic modifications [32,33,34] and on radiological findings [35].…”
Section: Discussionmentioning
confidence: 99%
“…Several research groups over the last 10 years focused on the identification of other bacterial strains that could shed new light on CRS etiology and on the relationship between AH and CRS. An interesting study by Nia and colleagues focused on Clamydophila pneumoniae , this uncommon infection can lead to CRS in the pediatric population, particularly in middle east countries [22]. The group demonstrated that adenoids can act as a reservoir for Clamydophila pneumoniae , and cause rhinosinusitis concomitant with AH.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant anaerobic flora was peptostreptococcus in all studies, while the anaerobic Gram- negative bacilli were the second most common factor in most studies ( 23 - 25 ). Furthermore, other studies showed that the most common causes of rhinosinusitis were Staphylococcus aureus and Pneumococcus ( 36 , 37 ). These findings suggest that the flora implicated in odontogenic sinusitis are very similar to the flora in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%